Pengaruh Intensitas Penggunaan Smartphone dan Kesepian terhadap Nomophobia pada Generasi Z di Kota Padang - Yola Yolanda Nelta; Free Dirga Dwatra (Lembaga Yasin AlSys, 2026)
Smartphone use has become an integral part of the lives of Generation Z, yet studies that specifically link smartphone use intensity and loneliness as predictors of nomophobia in local contexts remain limited. This study aimed to analyze the influence of smartphone use intensity and loneliness on nomophobia among Generation Z in Padang City. A quantitative survey design was employed, involving 400 Generation Z respondents aged 15–30 years selected through purposive sampling. Data were collected using the Indonesian version of the Nomophobia Questionnaire (NMPQ-10) adapted by Warsah et al. (2023), a smartphone use intensity scale developed by Oktavia (2024), and the UCLA Loneliness Scale Version 3 adapted by Pramitha (2018). Data were analyzed using multiple linear regression. The results showed that smartphone use intensity and loneliness had a positive and significant effect on nomophobia (sig. = 0.000 < 0.05), indicating that higher levels of smartphone use intensity and loneliness are associated with a greater tendency toward nomophobia. These findings contribute to a better understanding of nomophobia as a psychological phenomenon shaped by the interaction between technology use behaviors and individuals’ psychological conditions and, in practical terms, underscore the importance of healthy smartphone use management and the strengthening of social interaction quality among Generation Z as efforts to prevent nomophobia.